Bridging national climate targets and firm-level decisions: An agent-based model of China’s steel decarbonization pathways - Xiao Liu; Jinhong Du; Lingling Lv; Jingnan Hu; Xingang Liu (Proceedings of the National Academy of Sciences, 2026)
China’s steel sector is pivotal to national and global climate goals, yet decarbonization is constrained by entrenched coal-based processes and regional disparities. Top–down and bottom–up models often neglect firm-level heterogeneity and behavioral dynamics. Here, we develop an agent-based model linking policy signals—carbon caps, pollution standards, and resource limits—with firm-level investment decisions. We evaluate four scenarios combining current and strengthened climate and air targets with neutral or accelerated technology progress. All scenarios achieve deep CO 2 reductions (90 to 95% by 2060), but only the integrated policy-plus- technology pathway eliminates blast furnaces before midcentury, achieving the steepest declines. Policy- or technology-only pathways entail trade-offs, including lock-in to carbon capture and storage or delayed reductions. Our results show that synchronizing stringent climate policy with rapid technology cost declines is essential to steer China’s steel industry toward a carbon-neutral trajectory.